2011
DOI: 10.1128/aem.05428-11
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Protection against Sepsis by Probiotic Therapy and Stimulation of a Novel Bacterial Phylotype

Abstract: Prophylactic probiotic therapy has shown beneficial effects in an experimental rat model for acute pancreatitis on the health status of the animals. Mechanisms by which probiotic therapy interferes with severity of acute pancreatitis and associated sepsis, however, are poorly understood. The aims of this study were to identify the probiotic-induced changes in the gut microbiota and to correlate these changes to disease outcome. Duodenum and ileum samples were obtained from healthy and diseased rats subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
(26 reference statements)
2
34
0
1
Order By: Relevance
“…We hypothesized that long-term administration of PPI is associated with both SIBO and C. difficile infection. Changes of small intestinal microbiota composition are known to be prominent in the terminal ileum,18 and in a study, SIBO and C. difficile colonization as the terminal ileal microbiota has been evaluated 19. To date, microbiota changes in terminal ileum with PPI administration could be summarized as an increase of Firmicutes ( Lactobacillus or Clostridium ) and/or a decrease of Bacteroidetes 9.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that long-term administration of PPI is associated with both SIBO and C. difficile infection. Changes of small intestinal microbiota composition are known to be prominent in the terminal ileum,18 and in a study, SIBO and C. difficile colonization as the terminal ileal microbiota has been evaluated 19. To date, microbiota changes in terminal ileum with PPI administration could be summarized as an increase of Firmicutes ( Lactobacillus or Clostridium ) and/or a decrease of Bacteroidetes 9.…”
Section: Discussionmentioning
confidence: 99%
“…ilealis CRIB T from the small intestine of a rat (Gerritsen et al 2014). In rats, this species was identified to be a dominant member of the ileal microbiota (Gerritsen et al 2011b). Here we applied a holistic systems biology approach, involving several fields of experimental and theoretical biology, to study R. ilealis CRIB T .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to the limited number of available human datasets and the low prevalence of R. ilealis-like 16S rRNA gene sequences in ileal biopsy samples, it was not possible to find positive or negative correlations between prevalence and/or abundance of R. ilealis and specific human diseases. Gerritsen et al (2011b) have shown by 16S rRNA gene sequence-based analysis that R. ilealis CRIB T is a dominant member of the small intestine microbiota in rats, especially in the ileum.…”
Section: Prevalence Of R Ilealis In Human Datasetsmentioning
confidence: 99%